PENGARUH PENAMBAHAN CAMPURAN TEPUNG LIMBAH IKAN TUNA PADA PAKAN KOMERSIL TERHADAP PERTUMBUHAN IKAN LELE (Clarias sp.) - Adenia Cahyatie Aprillia; Eri Yusni (Program Studi Manajemen Sumberdaya Perairan, Fakultas Pertanian Universitas Sumatera Utara, 2018)
Catfish is a freshwater species that is widely cultivated and consumed because easy to process, and very popular in the society. One of many hindrances in aquaculture of catfish for business is that the feed frequently used by the community costs much, resulting in farmers using feed pellets like tuna-waste flour mixture as an alternative additional feed. Therefore, this research aims to determine the sufficient usage of the tuna-waste flour mixture in commercial feed to growth of catfish as well as the growth increase and the survival rate of catfish with additional tuna-waste flour mixture in its feed. This research was conducted on April to June 2018. The design were used Complete Randomized Design with 3 treatments and 3 repetitions, namely P1 treatment (80% Commercial Feed + 20% Tuna-Waste Flour), P2 (65% Commercial Feed + 35% Tuna-Waste Flour), P3 (50% Commercial Feed + 50% Tuna-Waste Flour). Statistic analysis were used the SPSS version 21.0 and the result was analyzed by using Analysis of Variance (ANOVA) and the Duncan test. The result of the research data shows that the most significant increase was found in P3 treatment, with 8 cm average increase in length and of 24.71 gr average increase in weight and the highest survival rate was found in P3 treatment as higher as 80.56% as well as FCR is 1.31%.Keyword : Catfish (Clarias sp.), Tuna Fish Waste Flour, Growth Rate, FCR